Economic impact of cross compliance in the field of animal welfare (Acts C18 and C16) - Speroni, Marisanna; Capelletti, Maurizio; Bruni, Antonio; Degano, Luigi (Italian Journal of Agronomy, 2015)
The paper reports the results of assessment of animal welfare at farm level on two dairy cattle farms, identification of structural and management actions to improve the animal welfare and estimate of the costs of such actions; furthermore the economic impact of the potential support under measure 215 of the Rural Development Plan was also simulated. At the time of assessment, no severe break of compliance was detected at the two farms; however some weaknesses were identified and improvement were proposed in order to maintain the current animal welfare status and avoid future failures. The two use cases showed that investments to improve animal welfare were partly self funded in the mid and long term due to the higher milk yield and the better animal health that were expected as consequence; however, in the short term, a large part of expenses was fully borne by farmers if not supported by a public grant or higher market prices. The support provided by the measure 215 is effective in rewarding farmers who undertake to adopt standards of animal husbandry which go beyond the relevant mandatory standards.